2012
DOI: 10.1080/00015458.2012.11680816
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Cause of Palpable Mass in Upper Abdomen—Giant Gastric Trichobezoar: Report of a Case

Abstract: A trichobezoar is a ball of swallowed hair that accumulates in the stomach and fails to pass through the intestines. Usually a trichobezoar presents in early satiety and malnutrition. Obstructive symptoms and manifestations of gastric outlet obstruction may occur. While small gastric trichobezoars may be removed via gastroscopy, large trichobezoars require surgical removal by gastrotomy through abdominal incision. We present a case of a successful mini-laparotomy removal of a giant gastric trichobezoar in a 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The first report of the successful endoscopic removal of a trichobezoar was for one that was relatively small, weighing only 55g [17]. Reports of successful endoscopic removal of trichobezoars in children are remarkably scarce - they are vastly outnumbered by case reports documenting unsuccessful attempts of endoscopic removal with or without fragmentation [8,14]. In our patient, two big masses were found, and endoscopic removal would have been challenging and not safe.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The first report of the successful endoscopic removal of a trichobezoar was for one that was relatively small, weighing only 55g [17]. Reports of successful endoscopic removal of trichobezoars in children are remarkably scarce - they are vastly outnumbered by case reports documenting unsuccessful attempts of endoscopic removal with or without fragmentation [8,14]. In our patient, two big masses were found, and endoscopic removal would have been challenging and not safe.…”
Section: Discussionmentioning
confidence: 80%
“…An analysis of the published case reports revealed that out of 40 cases in which endoscopic removal had been tried, only two (5%) were successful [8]. In one of these, a trichobezoar was successfully removed whole from the distal esophagus [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oesophagogastroduodenoscopy is indicated for definitive diagnostic and therapeutic purposes [ 6 – 10 ]. The procedure enables direct visual assessment of the mass and any ulcers.…”
Section: Discussionmentioning
confidence: 99%